2021
DOI: 10.21608/ejnf.2021.210840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocket Oil Addition on Productive and Reproductive Performances and Some Blood Parameters of Crossbred Ewes

Abstract: hirty-six crossbred ewes (½ finish Landrace x ½ Rahmani) aged 3-6 years and averaged live body weight (47.3 ± 1.73 kg) were randomly divided into three groups (12 ewes in each) according to their live body weight and reproductive history. All ewes were fed the same basal ration contained (CFM 50% and fresh berseem 50% on DM basis. Rocket oil (watercress oil) was received daily at levels 0.0,1.00 and 2 mg / 10 kg LBW for G1, G2 and G3, respectively. The experimental period was lasted for 150 days consisted of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…These observations agree with results obtained by Zanouny et al ( 2013 ), Fayed and Azoz ( 2018 ), and El-Gindy et al ( 2020 ) when either NS or ES seeds were added to the diets of rabbits or lambs. Similarly, the addition of ES oil significantly reduced both levels of cholesterol and triglycerides (Hafez et al, 2016 ; El-Badawy et al, 2018 and El-Giziry et al, 2021 ). Contrarily, Mustafa et al ( 2022 ) reported no significant effect on blood cholesterol and triglycerides with NS oil addition to the diets of Karadi lambs.…”
Section: Discussionmentioning
confidence: 97%
“…These observations agree with results obtained by Zanouny et al ( 2013 ), Fayed and Azoz ( 2018 ), and El-Gindy et al ( 2020 ) when either NS or ES seeds were added to the diets of rabbits or lambs. Similarly, the addition of ES oil significantly reduced both levels of cholesterol and triglycerides (Hafez et al, 2016 ; El-Badawy et al, 2018 and El-Giziry et al, 2021 ). Contrarily, Mustafa et al ( 2022 ) reported no significant effect on blood cholesterol and triglycerides with NS oil addition to the diets of Karadi lambs.…”
Section: Discussionmentioning
confidence: 97%